2023
DOI: 10.3390/su15097217
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Characteristics and Influencing Factors of the Coupling and Coordination of High-Quality Development in Eastern Coastal Areas of China

Abstract: China’s pursuit of sustainable and healthy economic growth requires the promotion of high-quality development. While many scholars have studied high-quality development, few have examined the coupling and coordination among its internal systems. The study aims to analyze the influencing factors of high-quality coordinated development, identify problem areas based on the five development statuses, and provide practical recommendations for optimizing the spatial layout of high-quality development in these areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The HQDI distribution of the subsystems confirms the severity of the spatial gradient differences. Some studies have paid attention to the CCD of high-quality development from different perspectives [17,[29][30][31][32][33][34][35][36][37]. These studies found that the CCD of high-quality development in some cities has not yet reached a high level [17,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HQDI distribution of the subsystems confirms the severity of the spatial gradient differences. Some studies have paid attention to the CCD of high-quality development from different perspectives [17,[29][30][31][32][33][34][35][36][37]. These studies found that the CCD of high-quality development in some cities has not yet reached a high level [17,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…They found that counties in Zhejiang Province have an intermediate coordinated degree [17]. Yuan et al found that most cities in the eastern coastal areas of China have weak coordination degrees and obvious internal differences [37]. However, there is a lack of measurement of the internal coupling coordination relationships between the high-quality development subsystems.…”
Section: Literature Reviewmentioning
confidence: 99%